Storying Science: Preparing STEM Students to Engage with Discipline-Specific and Public Audiences through the TED(x) Genre - Erica M Stone; Sarah E Austin (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Communicating about science with public audiences is becoming increasingly important for STEM students, both during their studies and once they enter a specific scientific workplace. Using two different general education writing courses as case examples, one at Middle Tennessee State University and one at the United States Air Force Academy Preparatory School, this article offers a model for how the rhetorical structure of the TED(x) presentation genre can be used to prepare STEM-focused students to better engage with non-expert audiences. Through narrative reflection and assignment examples, we build on Joshua Schimel’s framework for communicating science and provide a replicable model for general education writing faculty to ensure STEM students understand how to 1) Compel audiences to listen/read through engaging content; 2) Compose writing and speech genres in memorable structures; 3) Communicate with non-expert audiences with accessible language.